The Influence of Work Discipline on Employee Performance at the Towuti District Office, East Luwu Regency - Eka Viftah Riani; Akhmad Akhmad; Andi Mapatompo (Journal of Public Representative and Society Provision, 2026)
The purpose of this study is to ascertain how work discipline affects employee performance at the East Luwu Regency's Towuti District Office.  This study's foundation is founded on preliminary findings that point to issues with employee discipline, including tardiness, unexcused absences, and unacceptable behavior during working hours.  This study, which included 39 employees overall, took a quantitative approach using the census method.  Techniques for gathering data included recordkeeping, questionnaires, interviews, and observation.  According to descriptive results, the work discipline aspect's highest average value is found in the indication of adherence to agency regulations and time restrictions.  Regression analysis results, however, show that work discipline has a marginally favorable impact on employee performance.  Despite the importance of work discipline, this data suggests that its impact is not statistically significant enough, perhaps as a result of the presence of other elements like leadership, motivation, and the performance evaluation system.  Although this insignificance is consistent with a number of other studies, it runs counter to other results that indicate a considerable influence.  Other contributing factors include inadequate supervision, lax enforcement of rules, and a less-than-ideal workplace culture.  Therefore, in order to improve overall employee performance, work discipline must be improved through increased monitoring and ongoing coaching.